Science, technology & society in seventeenth century England - Merton, Robert K. (Humanities press, 1970)
With a new introduction by the author (emeritus, sociology, Columbia U., New York City), as well as the prefaces from the first edition in 1938 and a 1970 reprint, this classic work established the field of the sociology of science. The focus of the study is the role of Puritanism in unintentionally providing social and cultural support for newly emerging science in 17th-century England at a time when religion and science were considered irreconcilable.